Home

What is the correct answer?

4

11 + a(n - m) + 11 + a(m - n) = ? 

A. 0

B. 12

C. 1

D. am+n

Correct Answer :

C. 1



11 + a(n - m) + 11 + a(m - n)
= 11 + an  am + 11 + aman  
= am (am + an)+ an(am + an) 
= (am + an)(am + an) = 1. 

Related Questions

What is the correct answer?

4

If m and n are whole numbers such that mn = 121, the value of (m - 1)n + 1 is:

A. 1

B. 10

C. 121

D. 1000

What is the correct answer?

4

243)n5 × 32n + 1 9n × 3n  1 = ?

A. 1

B. 2

C. 9

D. 3n

What is the correct answer?

4

11 + a(n - m) + 11 + a(m - n) = ? 

A. 0

B. 12

C. 1

D. am+n

What is the correct answer?

4

If x = 3 + 22, then the value of x - 1x is: 

A. 1

B. 2

C. 22

D. 33

What is the correct answer?

4

xbxc (b + c - a) . xcxa (c + a - b) .xaxb(a + b - c) = ? 

A. xabc

B. 1

C. xab+bc+ca

D. xa+b+c

What is the correct answer?

4

The value of [(10)150 ÷ (10)146]

A. 1000

B. 10000

C. 100000

D. 106

What is the correct answer?

4

(25)7.5 × (5)2.5 ÷ (125)1.5 = 5?

A. 8.5

B. 13

C. 16

D. 17.5

What is the correct answer?

4

(256)0.16 × (256)0.09 = ?

A. 4

B. 16

C. 64

D. 256.25

What is the correct answer?

4

(0.04)-1.5 = ?

A. 25

B. 125

C. 250

D. 625

What is the correct answer?

4

11 + x(b - a) + x(c - a)   + 11 + x(a - b) + x(c - b) + 11 + x(b - c) + x(a - c) = ? 

A. 0

B. 1

C. xa-b-c

D. None of these